Traumatic dislocation and hip fracture in a paediatric patient and its subsequent sequels, case report - Clavijo Díaz, Gerbert Augusto; Cuenca Castro, Jaime Fernando; Jojoa Ríos, José Danilo (Revista Colombiana de Ortopedia y Traumatología, 2017)
A 9 year-old patient who suffered a car accident with high-energy impact, causing a right hip fracture, class II in Delbet and Colonna classification, with posterior dislocation of the femoral head, acetabulum and capital fractures, as well as labrum damage. Initially, it was impossible to achieve a closed reduction of the fracture, therefore an open reduction and internal fixation was performed. In post-operative follow-up, femoral head avascular necrosis was detected. Although uncommon, there are hip bone fractures in children in our area. This means that it is essential to know the impact of this condition the moment the injury occurs, as well as the complications that it can cause even if a proper surgical management is provided. Evidence level: IV.